Is Spartina alterniflora eradication project in Chongming Island a nature-based solution? - Dong-Fan Xu; Qi Yuan; Ling-Wen Lu; Bing Tan; Ming Ge; Jing-Yi Chen; Ying-Ying Hao; Si-Qi Zhou; Ling-Sang Sheng; Xing-Xing Cai; Bin Zhao (Nature-Based Solutions)
Invasive species profoundly impact ecosystems globally, not only threatening biodiversity by displacing native species but also disrupting ecological balances and imposing significant economic burdens. This has led countries to actively combat these pervasive threats. In China, Spartina alterniflora, an invasive species, has taken over more than 70 % of the coastal zone in just 50 years, especially in salt marsh. This study aims to assess the Spartina alterniflora eradication project in Dongtan of Chongming Island, Shanghai, based on the IUCN Global Standard for Nature-based Solutions (NBS). To ensure the comprehensiveness and diversity of the assessment process, stakeholders with diverse backgrounds were invited. The Dongtan project was qualitatively evaluated using the IUCN self-assessment tool for its adherence to the IUCN NBS Standard, identifying its strengths, weaknesses, improvement areas, and contributions to the national eradication campaign. The results show that the Dongtan Project closely aligns with the NBS standard, achieving an 88 % match, and demonstrates excellence in addressing societal challenges, enhancing biodiversity, and offering multiple benefits. Nevertheless, improvements can be made in Economic Feasibility (Criterion 4), Inclusive Governance (Criterion 5), and Balance Trade-offs (Criterion 6). The study underscores the importance of employing NBS standards for self-assessment in the project design phase, which facilitates the identification and refinement of potential design issues. The success of the Dongtan Project, exemplified by its effective Spartina alterniflora eradication strategies, serves as a compelling model for similar national campaigns.